Pattern and Risk Factor associated with Congenital Anomalies among Young Infants Admitted in Dhulikhel Hospital - Singh, Srijana Dongol; Shrestha, Ranendra Prakash Bahadur; Poudyal, Prithuja; Sradanandha, Sanjel; Shrestha, Shrinkala (Birat Journal of Health Sciences, 2019)
Introduction: Birth defects are defined as structural and functional defects that develop during the organogenesis periods and present at birth or detected later in life. They are an important cause of morbidity and mortality in infants. The known causes of birth defects are mostly genetic effect modified by environmental factors which may be prevented. Objective: The main objective of the study was to determine the association of certain risk factors with birth defects occurring in newborn and infant seeking care in Dhulikhel Hospital, Kavre, Nepal. Methodology: This is a hospital based, cross sectional and comparative study involving 219 young infant below 2 months of age admitted in the Dhulikhel Hospital, Kathmandu University Hospital. We enrolled infants admitted at Neonatal intensive care unit, Neonatal ward, and neonates staying with mother in post natal wards, from 1stJanuary 2015 to 31stDecember 2017. Results: Incidence of congenital malformations involvement of neonates in our hospital was 1.1% among the live births. The most frequent was cardiovascular systems 29(26.8%) followed by musculoskeletal system 17(15.7%) and face 15(13.8%). Less than 4 in number of Antenatal visit (p=0.017), not using folic acid during early pregnancy (p<0.001) and low socioeconomic conditions (p<0.001) were significantly associated with congenital malformations. Among all congenital anomalies complex congenital heart disease has poor outcome. Conclusion: The most common congenital defects involved cardiovascular and musculoskeletal system. Lack of antenatal visit, lack of folic acid during periconceptional age and low socioeconomic conditions are the most common risk factors identified for congenital anomalies.